In de schaduw van Artus Quellinus. Opnieuw Gerrit Lambertsen van Cuilenborch (Bulletin KNOB, 2017)
In KNOB Bulletin 115 (2016), Dirk de Vries set about drawing the sculptor and architect Gerrit Lambertsen van Cuilenborch (1597–1657) out of the shadow of Hendrick de Keyser, one of whose chief assistants he had been. In his article, De Vries attributed the ‘Dolhuysvrouw’ (Madhouse Woman) or De Razernij (Frenzy), a statue from the garden of the Amsterdam Madhouse, currently in the Rijksmuseum, to Lambertsen and dated it before his departure for Kampen around 1627/28. Neither attribution nor dating is persuasive, however, and both ignore more recent insights. On stylistic grounds – the borrowing from Italian examples and similarities with the work of Rubens and Artus Quellinus for the Palace on the Dam – De Razernij should be attributed to the latter sculptor and his studio and dated post-1650, nearly 25 years after Lambertsen had left Amsterdam. Moreover, there are no convincing stylistic parallels with Lambertsen’s documented works. Support for the post-1650 dating comes from a series of illustrations or descriptions in Amsterdam publications from the 1660s onwards. De Razernij is first mentioned in the stadsbeschrijving (city description) of Amsterdam penned by M. Fokkens (1662), and subsequently in those by O. Dapper (1663), T. Van Domseaer (1665), C. Commelin (1693) and J. Wagenaar (1765). It is also noteworthy that on the large and detailed map of Amsterdam by Balthasar Florisz from 1625, the Dolhuys is visible, but not De Razernij. Finally, echoes of the statue are to be found in Rombout Verhulst’s relief (dated 1660) for the Pesthuis (Plague House) in Leiden, and in a statue at Schloss Herrenhausen (Hanover) from 1702/10.